On the legal concept of dietary supplements - Łata, Monika (Przegląd Prawa Rolnego, 2023)
The purpose of this study was as an assessment of the legal concept of a dietary supplement applicable in European Union law. For this purpose a comparative analysis of the concept of dietary supplements in EU law as well as in the laws of the United States of America, the People’s Republic of China and Australia was carried out. Each of these three latter countries presents a model that differs to a greater or lesser extent from the European model. It has been found out that the principal difficulty in identifying and defining the concept of dietary supplements in the European Union is the lack of a solid scientific basis defining their impact on the human body and the ambiguity of results of clinical studies concerning their use, often based on mere speculation. Hence the postulate to revise the unclear parts of the EU definition of a food supplement and to precise the regulation on its composition.